2010
DOI: 10.4028/www.scientific.net/amr.152-153.81
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic Bismuth Ferrite Nanoparticles: Rapid Sintering Synthesis, Characterization, and Optical Properties

Abstract: The homogeneous multiferroic BiFeO3 nanoparticles with average particle size of 85 nm have been successfully synthesized by a simple sol-gel route. The prepared sample was characterized by a variety of techniques, such as X-ray diffractometry, thermogravimetric analysis and differential thermal analysis, differential scanning calorimeter analysis, scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy. The obtained results shows that rapid sintering and subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, the maximum magnetic susceptibility at 20 K in the zero field cooling (ZFC) curve, reported by Da Silva et al, differs from that reported at 50 K by Prado et al and that obtained at 85 K by Park et al , At the present, the reported band gap energy values for BiFeO 3 NPs and thin films are contradictory with regard to the expected qualitative dependence on the material dimensions (see Table S1). ,, It should be expected that the smaller the NPs the higher the band gap energy value, but the reported values do not show this trend. In the particular case of BiFeO 3 NPs, there is no agreement in theoretical considerations whether the electronic transitions are direct or indirect, see Table S1.…”
Section: Introductionmentioning
confidence: 96%
“…However, the maximum magnetic susceptibility at 20 K in the zero field cooling (ZFC) curve, reported by Da Silva et al, differs from that reported at 50 K by Prado et al and that obtained at 85 K by Park et al , At the present, the reported band gap energy values for BiFeO 3 NPs and thin films are contradictory with regard to the expected qualitative dependence on the material dimensions (see Table S1). ,, It should be expected that the smaller the NPs the higher the band gap energy value, but the reported values do not show this trend. In the particular case of BiFeO 3 NPs, there is no agreement in theoretical considerations whether the electronic transitions are direct or indirect, see Table S1.…”
Section: Introductionmentioning
confidence: 96%